Reduction of dark current in Ge-on-Si avalanche photodiodes using a double mesa structure - Wanitzek, Maurice; Hack, Michael; Ramachandra, Harishnarayan; Seidel, Lukas; Schwarz, Daniel; Schulze, Jörg; Oehme, Michael (Proceedings of SPIE - The International Society for Optical Engineering, 2024)
We demonstrate Ge-on-Si avalanche photodiodes based on a separate absorption, charge, and multiplication structure using a novel double mesa structure. This double mesa structure effectively confines the electric field inside the diode, as confirmed through simulation data. This leads to a reduced contribution of charge carriers from interface states at the etched sidewalls to the dark current. The diodes exhibit a dark current reduction by a factor of 7 compared to a standard single mesa structure, while the optical properties remain unchanged. At a wavelength of 1310 nm, a maximum optical responsivity of 10.1 A/W, corresponding to a gain of 46, is achieved. Temperature-dependent dark current measurements showed an increase of the underlying activation energy from 0.13 eV to 0.28 eV. This results to a dark current of 0.14 nA at a temperature of 170 K and a bias voltage of 95 % VBD, which is approximately 100 times smaller than that of the single mesa APDs at 12.7 nA.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Avalanche photodiodes (APDs); Dark current; Electric field; Germanium; Photodetectors; Short-wave infrared; Single-photon detection